Balancing interests of actors in the ocean tuna value chain of Khanh Hoa province, Vietnam. (December 2018) - Thi Nguyen, Kim Anh; Jolly, Curtis M.
Abstract: The exploitation of ocean tuna has become one of the most important fisheries, in terms of foreign income generation, in Khanh Hoa province. This paper examines the structure, conduct, and performance (SCP) of the tuna value chain within a value chain governance framework to answer the research questions: (a) what is the nature of the tuna value chain in Khanh Hoa province, (b) who are the actors involved in the ocean tuna value chain? (c) What type of market structure is in place and what is its effect on product flow and market performance. Results show that actors operate in an imperfectly competitive market and earn profits from their operation, but the intermediaries receive the most in comparison to their investment expenditure. Processing companies benefit more when they buy directly from the fishermen and they face many difficulties in exporting ocean tuna. Highlights: Tuna is an important exports species in Vietnam. Governance of fisheries affects the Structure, Conduct and Performance of the value chain. The structure, conduct and performance may vary among fishers, intermediaries and processors. Profitability of markets depends on financial and social relationships among the participants. Policy must be formulated to ensure that tuna fisheries remain sustainable.